Stockbridge dampers for extending the fatigue life of a cable at St Nazaire cable stayed bridge. (November 2022) - Berthellemy, Jacques; Siegert, Dominique; Berton, Édouard; Quentin, Pierre
Abstract: The failure of a stay cable on the Saint-Nazaire bridge is investigated in detail. In 2000, fatigue cracks that had cut many wires led to a first replacement, alike to the initial, of the H32 stay cable. Examination of the deposited locked coil strand showed that fretting fatigue was involved in the wire breaks. The cause of the failures at the anchorages is discussed/studied in depth in the paper. Bending moments of the rigid cable, at its exit from the anchorage socket were proven to be the source of the fatigue stress due to vibrations induced by vortex detachments (VIV: Vortex Induced Vibrations). As wires ruptures occurred again in 2017 in the new H32 stay cable at the same place, further studies on dampers were carried out. After numerical simulations, the "Stockbridge" damper became a good candidate for attenuating the amplitude of vibrations. It could indeed be designed to fit the required frequency range between 30 and 35 Hz.